2019
DOI: 10.3390/app9040655
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Multi-Temporal Sentinel-1 SAR Parameters to Crop Height and Canopy Coverage

Abstract: The Polarimetric Synthetic Aperture Radar technique has provided various opportunities and challenges in agricultural activities mainly on crop management. The aim of this study is to investigate the sensitivity of 10 parameters derived from multi-temporal Sentinel-1 Synthetic Aperture Radar (SAR) data, to crop height and canopy coverage (CC) of maize, sunflower, and wheat. The correlation coefficient values indicate a high correlation for maize during the early growing stage. The coefficient determinations (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(86 citation statements)
references
References 29 publications
4
77
2
3
Order By: Relevance
“…The quad-pol Radar Vegetation Index (RVI) proposed by Kim and van Zyl (2009), was modified for dual-pol SAR data (Trudel et al, 2012) as, 4σ 0 HV /(σ 0 HH + σ 0 HV ). Later with Sentinel-1 like dual-pol data (VV-VH), few studies used the alternative formulation as, 4σ 0 VH /(σ 0 VV + σ 0 VH ) (Nasirzadehdizaji et al, 2019;Gururaj et al, 2019). Nevertheless, these studies are driven by the utilization of the cross-polarized component of the received wave.…”
Section: Introductionmentioning
confidence: 99%
“…The quad-pol Radar Vegetation Index (RVI) proposed by Kim and van Zyl (2009), was modified for dual-pol SAR data (Trudel et al, 2012) as, 4σ 0 HV /(σ 0 HH + σ 0 HV ). Later with Sentinel-1 like dual-pol data (VV-VH), few studies used the alternative formulation as, 4σ 0 VH /(σ 0 VV + σ 0 VH ) (Nasirzadehdizaji et al, 2019;Gururaj et al, 2019). Nevertheless, these studies are driven by the utilization of the cross-polarized component of the received wave.…”
Section: Introductionmentioning
confidence: 99%
“…Time-series backscatter analysis gives very useful information when one crop type in various fields is intended to be observed in terms of the monitoring programs and management practices. The results also indicate that there is relationship between Sentinel-1 SAR backscatter values and crop variables such as crop height and crop coverage during the different phonological stages (Nasirzadehdizaji, 2019).…”
Section: Sar Backscattering Analysismentioning
confidence: 73%
“…Polarimetric indicators derived from S-1 data are not very well investigated over wheat and have shown moderate results for monitoring biophysical parameters compared to VV, VH and the VH/VV [6,7,21]. Nasirzadehdizaji et al [21] found moderate correlations between polarimetric parameters (entropy, anisotropy and alpha decompositions) and wheat height during the early growth stage.…”
Section: Introductionmentioning
confidence: 99%